The Effect of Mineral Addition in Fermentation of Sorghum Grain with Tempeh Yeast on Nutrient Digestibility in Layer Chicken - Utama, CS; Estiningdriati, I; Yunianto, VD; Murningsih, W (ANIMAL PRODUCTION, 2007)
The aim of the research was to study nutrient digestibility of fermented sorghum added with Ramos mineral in layer chicken. The experiment was in vivo using a Completely Randomised Design with 4 treatments. Each treatment has 5 replicates. The feed was given by force feeding method. Results showed that TO, T1, T2, and T3 have no significant effects (P>0.05) on the digestibility of crude protein, fat, and fiber. The digestibility of crude protein was 80.83%; 74.97%; 77.16% and 75.98%; fat: 77.40%; 79.14%; 85.19% and 86.07%; and fiber: 76.74%; 73.10%; 72.57% and 79.52%, for TO, T1, T2, and T3, respectively. In conclusion, addition of Ramos mineral in sorgum grain fermented with tempe yeast resulted in similar crude protein, fat and fat digestibility by layer chicken. (Animal Production 9(1): 14-17 (2007) Key Words : mineral, sorghum, fermentation, digestibility